Coupling a biochar filter to a leach bed reactor for anaerobic digestion of chicken litter. (February 2023) - Collins, Ben A.; Birzer, Cristian H.; Kidd, Stephen P.; Hall, Tony; Medwell, Paul R.
Abstract: In this study, coupling a biochar-packed anaerobic filter (AF) to a batch leach bed reactor (LBR) is investigated as a pragmatic method for biochar application to enhance high-solids anaerobic digestion of chicken litter. Recirculating leachate through a biochar filter reduced solid retention time by 45 % compared with a batch system without recirculation. The key benefit of biochar over inert filter media was the capability to reduce hydrogen sulfide production by 37 % overall; 25 % in the LBR, and 93 % in the AF. No significant differences in methane yield were observed. Biogas produced in the biochar AF was of higher quality with a maximum hydrogen sulfide content of 188 ppm and peak methane content of 73 %. However, majority of the biogas was produced in the LBR due to poor phase separation. Further research is required to increase biogas production in the AF and/or reduce hydrogen sulfide production in the LBR. Graphical abstract: Unlabelled Image Highlights: Biochar filter coupled to a leach bed reactor for chicken litter anaerobic digestion. The biochar filter reduced cumulative hydrogen sulfide production by 37 %. Biochar maintained hydrogen sulfide content below 188 ppm in the anaerobic filter. Recirculation through a filter maintains methane yield and increases production rate.